2021
DOI: 10.4103/jfmpc.jfmpc_246_21
|View full text |Cite
|
Sign up to set email alerts
|

Are myths surrounding long-acting reversible contraception the reason for a huge unmet need for spacing pregnancies?

Abstract: Background: Long-acting reversible contraceptives (LARC), a highly effective class of contraceptives, has a limited uptake by few couples due to lack of awareness, unavailability, and myths surrounding their application and side effects. Aims: This study was undertaken to understand and to clear myths of LARC among patients as well as to assess the knowledge, attitudes, practices, and preference. Materials and Methods: A hospital-based cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Myths and misconceptions about LARCs’ use, such as risk of cancer, genital tract infections, altered sexual function, and delayed conception following discontinuation, contribute to negative attitudes toward LARCs. [ 29 , 30 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myths and misconceptions about LARCs’ use, such as risk of cancer, genital tract infections, altered sexual function, and delayed conception following discontinuation, contribute to negative attitudes toward LARCs. [ 29 , 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…Myths and misconceptions about LARCs' use, such as risk of cancer, genital tract infections, altered sexual function, and delayed conception following discontinuation, contribute to negative attitudes toward LARCs. [29,30] After controlling for confounding factors, the study identified various predisposing, enabling, and need factors, that were significantly associated with the use of LARCs among married women with no desire for children in the study setting. The study showed that women with some level of formal education were more likely to report the current use of LARCs than those with no formal education.…”
Section: Discussionmentioning
confidence: 99%